Social media disinformation in the perspective of Islamic Communication: A Documentary Review of the Social Dilemma - Rita Absari; Andre Novie Rahmanto; Ignatius Agung Satyawan (SAHAFA: Journal of Islamic Communication, 2026)
This study investigates the impact of disinformation on social media on adolescents’ mental healthby analyzing the documentary film The Social Dilemma as a case study. A qualitative descriptive approachwas employed, focusing on the interpretation of scenes that reflect adolescents’ psychological dynamics inresponding to disinformation. The findings reveal four major themes: (1) anxiety triggered by the need forsocial validation, (2) social comparison leading to feelings of inferiority, (3) pressure to construct a “perfect”self-image aligned with unrealistic media standards, and (4) emotional instability caused by exposure to falseinformation. These findings align with the Halo Effect theory, which explains how negative perceptions of a single aspect of the self can expand into negative overall self-assessment, thereby reinforcing anxiety anddissatisfaction. From the perspective of Islamic communication, the results highlight the relevance of theprinciple of tabayyun (verification of information) as stated in Qur’an Surah Al-Hujurat: 6, along with thevalues of qana‘ah (contentment), muraqabah (self-awareness before God), and ihsan (striving for excellencewith sincerity) in maintaining adolescents’ psychological balance in the digital era. Theoretically, this researchintegrates social psychology with Islamic communication ethics, while practically, it provides insights fordesigning Islamic-based digital literacy strategies to protect youth mental health from the negative impactsof disinformation. Keywords: Disinformation, Social Media, Adolescent Mental Health, Halo Effect, Islamic Communication